DEVELOPMENT OF ARDUINO-BASED CENTRIFUGE WITH AUTOMATIC FEATURES - Demarwan, Rizky Tri; Ma’murotun, Ma'murotun (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2025)
This paper is aimed to designing and manufacturing a laboratory tool called Centrifuge Aircraft based on Arduino Uno control system. This machine is basically used to separate substances that have different molecular weights. Blood particles in the blood will be split into plasma and serum. The speed and time settings for the module made by the author have been programmed according to the existing provisions. This research is an experimental, observational study. The observation method is to measure directly on the tool using observation guidelines. In this case, the rotational speed, measuring time, and excess temperature on the centrifuge will be measured with the existing measuring instruments in the laboratory. For example, completing an ABO blood sample requires a speed of 1000 RPM with a period of 1 minute. We use the DS18B20 sensor for temperature sensors. The accuracy of motor speed in this centrifuge design is 95.22%, and the accuracy level of the timer is 98.12%. This research is expected to simplify and reduce the budget for purchasing equipment.